Effects of volatile–char interactions on the evolution of char structure during the gasification of Victorian brown coal in steam - Zhang, Shu; Min, Zhenhua; Tay, Hui-Ling; Asadullah, Mohammad; Li, Chun-Zhu (Elsevier Science Ltd, 2011)
The purpose of this study is to investigate the effects of volatile–char interactions on the evolution of char structure during the gasification of Victorian brown coal in steam. A novel one-stage fluidised-bed/fixed-bed quartz reactor was employed to carry out the experiments in the presence and absence of volatile–char interactions. The effects of thermal annealing on char structure were also investigated under similar conditions. The structural features of char were evaluated using FT-Raman spectroscopy. The results indicate that the char structural features were considerably affected by volatile–char interactions, which was shown from the Raman band area or the ratios between the band areas. H radicals from the thermal cracking/reforming of volatiles are believed to play a vital role in the changes in char structure due to the volatile–char interactions. H radicals could penetrate into char matrix and favour the condensation of aromatic rings, which was the main reason for the decrease in the ratio of small (less than 6 fused rings) to large aromatic rings during the volatile–char interactions. The volatile–char interactions also greatly affected the concentrations of O-containing groups in char and thus significantly altered the observed Raman intensity of the char.